Histopathological Study of Endoscopic Biopsies - Rupendra Thapa; Mamta Lakhey; Pradeep Kumar Yadav; Prakash Kandel; Choodamani Aryal; Kamana Subba (Journal of Nepal Medical Association, 2013)
Introduction: Diseases of upper gastrointestinal tract are responsible for a great deal of morbidity and mortality. The histopathological study of endoscopic biopsies permits exact diagnosis for further management.The aim of this study is to find out the histopathological pattern of endoscopic biopsy. Methods: A descriptive study was conducted in consecutive endoscopic gastric biopsies in a Hospital over a period of one year. The patient of all ages and both sexes who underwent gastric biopsy during the study period was included. Results: Endoscopic biopsies were studied on patients of age ranging from 20 years female to 84 years male. The histopathology revealed non-neoplastic lesions 54 (67.5%) and neoplastic lesions 26 (32.5%). Most common non-neoplastic lesion noted was mild chronic gastritis 22(27.5%) followed by chronic active gastritis 15 (18.75%) while H. pylori was present in 13 (16.25%) and absent in 2 (2.5%). Conclusions: Mild chronic gastritis was the commonest lesion noted in non-neoplastic lesions and adenocarcinoma was the commonest neoplastic lesion in the endoscopic gastric biopsies. ______________________________________________________________________________________ Keywords: biopsy; endoscopy; gastritis; histopathological.